Dissimilatory nitrate reduction processes in surface sediments of shrimp ponds during the culture period - Sun, Dongyao; Huang, Jiafang; Luo, Min; Chen, Cheng; Lan, Xue; Hu, Weifang (Frontiers in Marine Science, 2022)
Intensive aquaculture in coastal estuaries has resulted in several ecological and environmental problems. However, there are relatively few studies on the process and contribution of nitrate (NO3-) reduction in sediment during the shrimp pond culture period. Three sediment NO3- reduction processes, denitrification (DNF), anaerobic ammonium oxidation (ANA), and dissimilatory NO3- reduction to ammonium (DNRA), were surveyed in three shrimp ponds of subtropical estuaries using nitrogen isotope tracing experiments. The rates of DNF, ANA and DNRA ranged from 2.87–18.11, 0.10–1.92, and 0.21–1.25 nmol N kg -1 h -1, respectively. DNF was responsible for 64.2–91.6% of the total NO3- reduction. Regarding environmental factors, C and N substrates, as well as salinity, significantly affected NO3- reduction. Our results provide a scientific foundation for understanding the mechanism of nitrogen cycling in the artificial aquatic environment of shrimp ponds.